Financial Performance Analysis of Universitas Siliwangi Using Ratio and Trend Evaluation for Fiscal Years 2023–2024 - Maria Christine Magdalena; Christina Tjia; Yanuard Putro Dwikristanto (Business Management, 2026)
This study aims to analyze the financial performance of Universitas Siliwangi, a public university operating under the Public Service Agency (BLU) framework, by employing financial ratio analysis and trend evaluation for the fiscal years 2023–2024. The analysis is based on the university’s statement of financial position, statement of activities, and cash flow statement to assess liquidity, operational efficiency, funding structure, and overall financial sustainability. The findings indicate that Universitas Siliwangi demonstrates a strong liquidity position, reflected in a substantial increase in current assets and liquidity ratios throughout 2024. Operational efficiency also improved as evidenced by reduced total expenses and a higher allocation of funds toward core educational service programs. Despite decreases in revenue and operational surplus due to shifts in funding dynamics, the university remains in a financially healthy condition. These results suggest that the financial management of Universitas Siliwangi has been effective; however, further optimization through diversified revenue streams and strategic long-term investment is essential to strengthen future financial sustainability.